A review of plants and essential oils effective as natural remedies against bedbugs - Bhirich, Nihal; Meknassi, Ghita Salime; Yafout, Mohamed; Elhorr, Hicham; Haj Said, Amal Ait; Mojemmi, Brahim (Indian Journal of Pharmacy & Drug Studies, 2024)
Called Cimex lectularius and Cimex hemipterus, the bedbug has made its return to daily life in many developed countries since the 1990s, although it had practically disappeared since the 1950s. The resurgence of bedbug infestations can be explained partly by the evolution of the lifestyle and by the mode of consumption favoring second-hand purchasing. One of the main factors behind their resurgence is the excessive use of synthetic insecticides with similar modes of action, which has led to the development of insecticide resistance. The application of synthetic insecticides indoors or in the environment is a public health concern due to the toxic effects that can result from prolonged exposure to these chemicals. It is for this reason that there is an increased demand from the public for the use of effective “green” products for urban pest control. Natural insecticides, including EOs are considered safe due to their low toxicity to humans and animals. Thanks to a search in ethnobotanical studies, we identified a list of 10 plants used in the fight against bedbugs: Lavandula latifolia spica, Corymbia citriodora, Syzygium aromaticum (L), Cymbopogon winterianus jowitt, Thymus vulgaris, Chrysanthemum cinerariaefolium, Phaseolus vulgaris, Oreganum vulgare L., Tagetes paluta L. and Cinnamomum camphora. The study of the literature that we subsequently carried out showed that these plants/essential oils/components act according to 4 mechanisms, namely: topical, neurological, mechanical or fumigant effects. We therefore conclude that the use of preparations of natural origin has the advantage of avoiding the toxic and polluting harm of substances of chemical and synthetic origin and that it is desirable to continue research and investigation of the composition details of its plants and essential oils.